ANALISIS PENGARUH MOTIVASI KERJA, FASILITAS SARANA PRASARANA BERUPA BARANG MILIK NEGARA (BMN) TERHADAP KUALITAS KINERJA MELALUI KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING DI LINGKUNGAN KANTOR WILAYAH KEMENTERIAN HUKUM DAN HAM KALIMANTAN SELATAN - Ogi Try Sugandi (KINDAI, 2023)
The purpose of this research is to prove and analyze the effect of Work Motivation, Facilities and Infrastructure on Performance Quality through Job Satisfaction in the Regional Office Environment of the Ministry of Law and Human Rights in South Kalimantan. The research method used is a survey research method. The population in this study were 138 employees in the Regional Office of the Ministry of Law and Human Rights in South Kalimantan by taking the entire population as a sample. Data collection techniques using a questionnaire that has met the requirements of the validity and reliability tests, using regression analysis. The results of the study show that work motivation and infrastructure have a significant effect on employee job satisfaction in the Regional Office of the Ministry of Law and Human Rights in South Kalimantan. Work motivation and infrastructure have a significant effect on the quality of employee performance in the Regional Office of the Ministry of Law and Human Rights in South Kalimantan. Job satisfaction has no significant effect on the quality of employee performance in the Regional Office of the Ministry of Law and Human Rights in South Kalimantan. The effect of work motivation and infrastructure in the form of state property on the quality of performance through job satisfaction is not significant, where job satisfaction cannot mediate the influence between work motivation and infrastructure and performance quality. Leaders are expected not to hesitate in giving praise and support or motivation to employees to be able to provide encouragement for performance in order to provide the best work results.